Draft Genomic Resources for the Brown Rot Fungal Pathogen Monilinia laxa - Lucia Landi; Stefania Pollastro; Caterina Rotolo; Gianfranco Romanazzi; Francesco Faretra; Rita Milvia De Miccolis Angelini (Molecular Plant-Microbe Interactions, 2020)
Monilinia laxa is the causal agent of brown rot on stone fruit, and it can cause heavy yield losses during field production and postharvest storage. This article reports the draft genome assembly of the M. laxa Mlax316 strain, obtained using a hybrid genome assembly with both Illumina short-reads and PacBio long-reads sequencing technologies. The complete draft genome consists of 49 scaffolds with total size of 42.81 Mb, and scaffold N50 of 2,449.4 kb. Annotation of the M. laxa assembly identified 11,163 genes and 12,424 proteins which were functionally annotated. This new genome draft improves current genomic resources available for M. laxa and represents a useful tool for further research into its interactions with host plants and into evolution in the Monilinia genus.